Don't Miss This! Red Flags in the Pediatric Eye Examination: Introduction and Essential Concepts. Issue 3 (3rd July 2019) - Christiansen, Stephen P.
ABSTRACT: Although the pediatric eye examination can be made more challenging by inattention, poor cooperation, sleep, or just the wiggles, these should never be justification for an inadequate assessment of the child. In fact, a challenging patient should make the examiner ever more careful to get a good history and to look carefully for potential red flags that should be examined in greater detail. Missing a history of diplopia, or not noticing an abnormal pupil, or blurred disc margins, to name a few, may delay the diagnosis and treatment of potentially life-threatening entities. In this symposium, red flags in the pediatric eye examination will be reviewed in depth with emphasis on diagnosis, testing, and referral.